José Uriel García y su concepto de estilo crespo como un fundamento del «arte nacional» (1934-1939) - Caparó Aragón, Marco Antonio (2022)
This article is based on the idea of ​​understanding the artistic narrative of José Uriel García exposed in La Prensa de Argentina, which is based on ideological content of a historical-artistic nature disclosed in telluric ideology essays. From this framework, the objective will be to propose the Crespo style as a national art, developed in the southern Peruvian highlands, through the implementation of educational policies disseminated in the San Antonio Abad University of Cusco (1910-1923) and as an influence of the Argentine thinker Ricardo Red. The analysis approach used an artistic historiography. In this sense, documents, magazines, newspapers and works by specialist authors were reviewed. In addition, twelve journalistic essays of La Prensa. The axis of inquiry will demonstrate that the existence of the Crespo style includes the national conjuncture, created from studies on the churches of San Miguel de Mamara and Santiago de Pomata, as well as painting, imagery, etc. As a result of this analysis, we conclude It that its validity allows us to affirm that it flourished in the first third of the 18th century, only in southern Peruvian small towns. The contribution states that the Crespo style was the national expression, created by artists of Indo-mestizo origin in their desire to represent pristine regional artistic expressions.